Hypertension is also fought at the pace of dance - Mario Pappagallo (Archives of Clinical Hypertension - Peertechz Publications, 2018)
Naples. Congress of the Italian Society for Cardiovascular Prevention (Siprec). Dance is the scene. Do not think of the teachers who start dancing, even if it would not hurt to give rhythm to scientifi c reports, but a new remedy to prevent high blood pressure or even lower it if it tends to rise above the norm.